IMPORTANCE OF DISTANCE EDUCATION TODAY - Baltayeva AnadjanTadjibayevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In this article, one of the advanced foreign experiences in education today is the integrative organization of education, the creation of a new psychological process, a new structure of activity through integration, any lower level of interdisciplinary communication, the study being studied. among certain didactic units within the scope of their subjects, the content of their study and the main areas of distance education and the use of distance education in education are discussed.